Effect of Turmeric Ethanol Extract Ointment (Curcuma Longa) on the Healing of Grade II Burns in Wistar Rats (Rattus Norvegicus) - Ji Junfeng; Florenly Florenly; Johannes Bastira Ginting; Fioni Fioni (Budapest International Research and Critics University, 2021)
Burns is still a choir for clinical nurses as severe burns have led to high postburn morbidity. In Indonesia, the death rate from burns is still high at about 40%, mainly caused by severe burns. Curcuma longa herbal products have several such antioxidants, anti-inflammatory, anti-cancer. The purpose of this study was to find out the phytochemical content and effect of turmeric Ethanol Extract Ointment (Curcuma longa Linn) in curing grade II burns in Wistar rats (Rattus norvegicus). This study is an experimental study with a pre and post-test control group design approach. This research was conducted at Riwandi Pet Shop and Animal House and Laboratoirum Taxonomy of Plants, Department of Biology, Faculty of Mathematics and Natural Sciences (FMIPA), the University of North Sumatra in February-March 2021. The study sampled 20 turmeric rhizomes and male Wistar rats (Rattus norvegicus) divided into 4 treatment groups. Independent variables of topical formulation (base ointment, nebacetin ointment®, Turmeric Ethanol Extract Ointment (Curcuma longa) 5% and Turmeric Ethanol Extract Ointment (Curcuma longa) 10%, as well as independent variables that include wound contraction and epithelial period. The results of phytochemical screening in turmeric found phytochemicals in the form of flavonoids, alkaloids, and tannins. The results of the study obtained significant differences in the epithelial period of the standard group, turmeric ointment 5% and 10% against the control group. However, in the turmeric ointment group and the standard group, there was no difference in epithelialization periods. This is evident from the value P < 0.05 (Value P = 0.028). Where the wound contraction rate of turmeric ointment is 10% better than nebacetin ointment as standard. But in both turmeric ointments, both 5% and 10% and nebacetin ointment as standard did not show significant differences in the parameters of the epithelial period.